Soil macropore structure plays divergent roles in fresh and decomposed particulate organic matter - Tianyu Ding; Zichun Guo; Zizhou Yu; Jiaqi Li; Jianli Liu; Xinhua Peng (Communications Earth & Environment)
Abstract Understanding fresh and decomposed particulate organic matter distributions and their response to macropore structure is crucial for soil carbon stocks. However, the roles of macropore structure in particulate organic matter fractions within aggregates and whether these processes are influenced by fertilization remain largely unknown. Here we investigated the effects of fertilization on particulate organic matter and macropore structures within 3-5 mm aggregates across five long-term field experiments (12 to 34 years) in China, using X–ray computed tomography. Manure application contributed to particulate organic matter accumulation and enhanced pore connectivity across five sites. 20%–69% of the fresh particulate organic matter was distributed within surface-connected pores. Decomposed particulate organic matter was predominantly distributed in isolated pores or matrix and influenced by its distance to pores. Our study highlights the divergent roles of macropore structure in fresh and decomposed particulate organic matter, offering enhanced insight into carbon stabilization within soil aggregates.